Perancangan Dan Pembuatan Komponen Mesin Pembuat Bakso Menggunakan Screw Conveyor Dengan Pemotongan Bakso Secara Mekanik - Jon Aristo; Nazaruddin Nazaruddin; Dedi Rosa Putra Cupu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Various efforts have been made to develop the efficiency of time and effort on making meatballs, including this machine a good time efficiency in making meatballs in which the meatball machine forms meatballs of 250 to 280 meatballs / minute. The principle working of this machine is iguite simple where the meatball dough will be input into the dough container and processed by a screw conveyor, when the meatball dough has pressure due to screw conveyor, the meatball dough will be forwarded to the meatball printing dies, and after the dough through the dies meatball printer, meatball will be cut by two plates that move horizontally, the cut meatballs will fall into a tub of boiled meatballs due to the gravitational force. The dimensions of the screw used in this machine a size diameter of 65 mm with a screw shaft diameter of 25.4 mm. With the dies thickness used, which is 25.5 mm, it can accept the load distributed from the screw so that the dimensions of dies used can be declared safe. With the rotational speed of the dies pulley used the same as the cutting speed of the meatballs so that the distance between the pulley dies and the meatball cutting pulleys is 150 mm with the belting size A-24 with a tensioner as far as 26.9 mm. The hand hand cutting angle will affect the distance of the blade where this angle is 43o Keywords: Dies, Screw Conveyors, Tensioners, Blades